Effect of Growth Rate and Wafering on Residual Stress of Diamond Wire Sawn Silicon Wafers - Kumar, Arkadeep; Prasath, R.G.R.; Pogue, Vanessa; Skenes, Kevin; Yang, Chris; Melkote, Shreyes N.; Danyluk, Steven (Procedia manufacturing, 2016)
The mechanical integrity of photovoltaic (PV) silicon wafers is critical to avoid failure during solar cell manufacturing. Residual stress present in wafers affects mechanical integrity. Residual stresses are generated during solidification of ingots and during the wafering or wire sawing process used to produce silicon wafers. In this paper, the residual maximum shear stress in diamond wire sawn photovoltaic multi-crystalline silicon wafers corresponding to different crystal growth rates and their pre-and post-etched conditions are analyzed. The full-field residual stress distributions in the wafers are measured using near infra-red transmission birefringence polariscopy. Results show that wafers corresponding to the high crystal growth rate are characterized by larger residual maximum shear stress. As the growth rate increases to two times the standard growth rate, the average residual stress increases by 43%. The increase in residual stress in the high growth rate wafers is attributed to the interaction of abrasives with more grain boundaries present in these wafers. Etching results in lower residual stress for all growth rates and ingot locations.